1988
DOI: 10.1161/01.cir.77.1.221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changes in afterload on systolic bulging.

Abstract: It has been previously shown that after acute coronary occlusion, the extent of systolic bulging is dependent on preload and the function of the remote nonischemic myocardium is influenced by the motion of the ischemic myocardium as well as by the loading conditions. To examine the isolated effects of changing afterload on the movement of acutely ischemic and nonischemic myocardium, seven open-chest, anesthetized dogs were paced from the left atrium at a rate of 100 beats/min after crushing of the sinus node. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…Therefore, the change in stroke volume, which was decreased by angiotensin II and increased by nitroprusside, seemed to depend on the change in ejection shortening in the non-ischemic region alone. Thus our results regarding the influence of change in afterload on regional wall motion differ in two major ways from data reported by Noma et al (1988b). First, our data indicate that isovolumetric shortening in the non--ischemic and ischemic regions changed in opposite directions when afterload changed, while they reported that lowering afterload increased isovolumetric shortening in the non-ischemic region and lessened systolic expansion in the ischemic region (Noma et al 1988b).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Therefore, the change in stroke volume, which was decreased by angiotensin II and increased by nitroprusside, seemed to depend on the change in ejection shortening in the non-ischemic region alone. Thus our results regarding the influence of change in afterload on regional wall motion differ in two major ways from data reported by Noma et al (1988b). First, our data indicate that isovolumetric shortening in the non--ischemic and ischemic regions changed in opposite directions when afterload changed, while they reported that lowering afterload increased isovolumetric shortening in the non-ischemic region and lessened systolic expansion in the ischemic region (Noma et al 1988b).…”
Section: Discussioncontrasting
confidence: 79%
“…Thus our results regarding the influence of change in afterload on regional wall motion differ in two major ways from data reported by Noma et al (1988b). First, our data indicate that isovolumetric shortening in the non--ischemic and ischemic regions changed in opposite directions when afterload changed, while they reported that lowering afterload increased isovolumetric shortening in the non-ischemic region and lessened systolic expansion in the ischemic region (Noma et al 1988b). Second, in the present experiment, ejection shortening in the ischemic region remained unchanged by changes in peak left ventricular pressure while their report showed a decrease in ejection shortening in the ischemic region when peak left ventricular pressure was elevated (Noma et al 1988b).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…On the other hand, the increase in the bulging in the ischemic region with the increase in heart rate can be partly explained by the reduction of the end-diastolic length (Ishikawa et al 1993). In the isovolumetric contraction phase, the increment of the shortening in the non-ischemic region has been explained by the augmentation of bulging in the ischemic region that is increased when the preload is decreased or the afterload increased (Lew and Ban-Hayashi 1985;Noma et al 1988a;Ishikawa et al 1993;Sakuma et al 1993). But when the heart rate increased, the increase of the bulging in the ischemic region was not accompanied by shortening in the non-ischemic region.…”
Section: Regional Wall Motion In the Isovolumetric Phasementioning
confidence: 99%